2016
DOI: 10.1371/journal.pone.0161658
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Methicillin-Resistant Staphylococcus aureus Diabetic Foot Infections in a Large Academic Hospital: Implications for Antimicrobial Stewardship

Abstract: IntroductionDiabetic foot infections (DFIs) are the leading cause of non-traumatic lower extremity amputations in the United States. Antimicrobials active against methicillin-resistant Staphylococcus aureus (MRSA) are recommended in patients with associated risk factors; however, limited data exist to support these recommendations. Due to the changing epidemiology of MRSA, and the consequences of unnecessary antibiotic therapy, guidance regarding the necessity of empirical MRSA coverage in DFIs is needed. We s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
34
2
3

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 14 publications
(18 reference statements)
2
34
2
3
Order By: Relevance
“…Treatment of staphylococcal diabetic foot infections with antibiotics is becoming increasingly difficult because of the widespread presence of antibiotic-resistant S. aureus strains (10,11,28). Previous reports have shown the potential of phages as an alternative or adjunctive therapy to treating bacterial infections in an animal model (29,30), but information regarding the treatment of human DFUs caused by MDR S. aureus using a phage cocktail topically is limited.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Treatment of staphylococcal diabetic foot infections with antibiotics is becoming increasingly difficult because of the widespread presence of antibiotic-resistant S. aureus strains (10,11,28). Previous reports have shown the potential of phages as an alternative or adjunctive therapy to treating bacterial infections in an animal model (29,30), but information regarding the treatment of human DFUs caused by MDR S. aureus using a phage cocktail topically is limited.…”
Section: Discussionmentioning
confidence: 99%
“…S. aureus is a virulent pathogen frequently isolated from DFU (5,9,10). A study in Australia found that two-thirds of DFU patients were infected with S. aureus, and nearly half were methicillin-resistant (MRSA), for which there are limited antimicrobial treatment options (11).…”
Section: Introductionmentioning
confidence: 99%
“…Доля S. aureus среди всех возбудителей гнойно-некротических осложнений синдрома диабетической стопы в первые сутки госпитализации составила 18,4%, на 5-50 сутки -23,7%. По результатам микробиологических исследований биоптатов пациентов с синдромом диабетической стопы за рубежом доля S. aureus составляет 15-50% [26], таким образом, наши результаты соответствуют общемировым. В плане распространенности полирезистентных микроогранизмов среди данной категории пациентов, в частности доли MRSA, БЛРС-продуцирующих энтеробактерий, МБЛположительных p. Pseudomonas, p. Acinetobacter, выделенных в первые сутки госпитализации и на 5-50 сутки, также существенных различий не выявлено (p > 0,05).…”
Section: Discussionunclassified
“…В США частота ампутаций, связанных с диабетом, составляет 66 тыс. случаев в год; в 50-70% случаев причиной ампутации стопы является гангрена [26]. Пребывание пациентов с сахарным диабетом и с гнойно-некротическими поражениями в стационаре на 50% дольше [8].…”
Section: Introductionunclassified
See 1 more Smart Citation